Attitude Ambivalence, Friend Norms, and Adolescent Drug Use - Hohman, Zachary P. (2014)
This study assessed the moderating effects of attitudinal ambivalence on adolescent marijuana use in the context of the theory of planned behavior (TPB). With data from the National Survey of Parents and Youth (N=1,604), two hierarchical multiple regression models were developed to examine the association of ambivalent attitudes, intentions, and later marijuana use. The first model explored the moderating effect of ambivalence on intentions to use marijuana; the second tested the moderation of ambivalence on actual marijuana use 1 year later. Results across both analyses suggest that ambivalence moderated the association of friend norms and subsequent adolescent marijuana use: friend norms were better predictors of marijuana intentions (β=0.151, t=2.29, p=0.02) and subsequent use when adolescents were attitudinally ambivalent about marijuana use (β=0.071, t=2.76, p= 0.006). These results suggest that preventive programs that affect the certainty with which adolescents holds pro- or antimarijuana attitudes may influence the likelihood of their resistance to, initiation, or continuance of marijuana use.